Assessment of prevalence of hypertension in an urban population: a cross sectional study in Indore city - Modiwala, Ashfaq; Deshpande, Ajit; Wavare, R. R.; Kantharia, S. L. (International Journal Of Community Medicine And Public Health, 2018)
Background: Hypertension is growing rapidly to epidemic levels in the developing countries, that’s why described by some clinicians as a ‘silent killer’. The objective of the study was to study the prevalence of hypertension among adults in urban area of Indore city. Methods: A community based survey was conducted among the 375 residents of urban population of Indore. Results: In our study 157 subjects were found to be hypertensive with the prevalence of 41.9%. Where; new cases of hypertension were found to be with prevalence of 15.7%. Out of which males were 44 (20.3%). Whereas, previously diagnosed 98 (62.4%) subjects were on anti-hypertensive medication and 59 (37.6%) newly diagnosed subjects who did not know they were having hypertension. Conclusions: The prevalence of hypertension in study subjects was 41.9%. 15.7% subjects didn’t know that they were having hypertension. 31.6% of hypertensive subjects were on irregular medication. It was found that lack of awareness, negative attitude of people for practicing modifiable risk factors associated with hypertension.